Phonics Made Easy (Grand Haven, Mich School Zone Interactive, 2005)
Children will have fun learning and practicing beginning phonics skills in this easy-to-use program
Ages 6+
System requirements for Windows: Pentium or faster ; Windows 95, 98 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 16-bit sound card ; 4X CD-ROM drive. System requirements for Macintosh: PowerPC 601 or faster processor ; System 7.5.5 or higher ; 24 MB RAM ; 50 MB free disk space ; 640x480, 16-bit color video ; 4X CD-ROM drive
1
Keywords: games -- audiovisual; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs